if f ( x ) = 3 1 ( f ( x + 1 ) + f ( x + 2 ) 5 ) and f ( x ) > 0 for all real values of x then l i m x → ∞ f ( x ) = b a
then a + b =
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
When x → ∞
f(x) = f(x+1) = f(x +2) = t(let)
Substituting in equation we will get
3t = t + t 5
t = 2 5
Problem Loading...
Note Loading...
Set Loading...
To Megh please upload the question clearly and close all the open brackets to avoid confusion. thankyou